2016
DOI: 10.1016/j.neulet.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status is associated with striatal dopamine D2/D3 receptors in healthy volunteers but not in cocaine abusers

Abstract: Positron emission tomography (PET) studies in animals and humans have shown that social status is associated with striatal dopamine D2/D3 receptor (D2/D3R) availability. That is, higher social hierarchy and higher scores on questionnaires assessing social status correlated positively with striatal D2/D3R availability in animals and humans respectively. Furthermore, subordinate monkeys were vulnerable to cocaine self-administration, suggesting that alternations in social hierarchy can change D2/D3R availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Another showed that subjective SES moderated an association between neural responses to perceived pain in others (a measure of empathy) and subsequent charitable donations (Ma et al 2011). However, with the exception of one study showing SES differences in a neural correlate of drug addiction (Wiers et al 2016), studies have not examined the neural correlates of BCD behaviours. To further understand the neural mechanisms of the BCD, it would be useful to examine socioeconomic differences in neural responses to decisions involving present-future trade-offs.…”
Section: Biological Mechanisms In the Bcdmentioning
confidence: 99%
“…Another showed that subjective SES moderated an association between neural responses to perceived pain in others (a measure of empathy) and subsequent charitable donations (Ma et al 2011). However, with the exception of one study showing SES differences in a neural correlate of drug addiction (Wiers et al 2016), studies have not examined the neural correlates of BCD behaviours. To further understand the neural mechanisms of the BCD, it would be useful to examine socioeconomic differences in neural responses to decisions involving present-future trade-offs.…”
Section: Biological Mechanisms In the Bcdmentioning
confidence: 99%
“…As can be seen from table 1, initial findings of a relationship between D2R and traits related to social behaviour have been corroborated in multiple studies when using antagonist radioligands. Specifically, a negative correlation has been reported between D2R and the social desirability scale of the Swedish University Scales of Personality (SSP) [33] and Lie scale of the Maudsley Personality Inventory (MPI) [18,34,35], a line of research that has also been extended to include measures of social status [36,37]. Interestingly, recent studies using the agonist radioligand [ 11 C]PHNO have shown patterns of the opposite direction [38,39].…”
Section: Correlative Studies: Personality Traitsmentioning
confidence: 99%
“…Other studies reported no differences in DAT [18] or receptors [19] in current smokers. Inconsistent results were also found between current cocaine users compared to healthy controls indicating lower DAT and receptor density in cocaine dependents [20][21][22] and abusers [23] or higher DAT in dependents [24][25][26] or no differences in dependent subjects [27][28][29] and cocaine users [30] compared to the control groups. Compared to healthy controls, evidence for significantly reduced DAT and receptors in MA users were found in some studies for currently MA dependent subjects [31][32][33][34], current MA abusers [35][36][37], chronic users [38] and former users or MA dependent subjects in rehabilitation [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%